1984
DOI: 10.1177/036354658401200408
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the incidence of recurrence of first time anterior shoulder dislocations with rehabilitation

Abstract: Studies of adolescent and young adult males sustaining primary anterior shoulder dislocations reveal the likelihood of recurrence to be virtually always above 50% and as high as 79% to 94%. Common among these investigations is the lack of a specific, rigidly adhered to rehabilitation program. During a 3 1/2 year period, 20 midshipmen at the United States Naval Academy sustained primary anterior shoulder dislocations. All participated in an identical treatment regimen which included a restrengthening program em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(88 citation statements)
references
References 4 publications
3
78
0
6
Order By: Relevance
“…Although some studies have suggested that prolonged immobilisation of the shoulder, 48 restriction of activity or an intensive programme of rehabilitation 6,49 may reduce the risk of recurrent instability, these measures have not been consistently effective. 4,7,50 Restriction of shoulder movement in a sling for a period of two to three weeks followed by a graduated rehabilitation programme is the accepted management of a primary dislocation in the young patient.…”
Section: Treatment Of the Initial Dislocationmentioning
confidence: 99%
“…Although some studies have suggested that prolonged immobilisation of the shoulder, 48 restriction of activity or an intensive programme of rehabilitation 6,49 may reduce the risk of recurrent instability, these measures have not been consistently effective. 4,7,50 Restriction of shoulder movement in a sling for a period of two to three weeks followed by a graduated rehabilitation programme is the accepted management of a primary dislocation in the young patient.…”
Section: Treatment Of the Initial Dislocationmentioning
confidence: 99%
“…About 5% of dislocations have an atraumatic origin (eg, minor incidents such as raising the arm or moving during sleep). 6,17,66,82 These individuals may have capsular laxity or altered muscle control of the shoulder complex or both. 55 Recurrent Dislocations An important complication of primary dislocation is subsequent recurrent dislocations.…”
Section: Epidemiologymentioning
confidence: 99%
“…47 There have been few studies investigating outcomes for exercise rehabilitation in the nonoperative management of primary traumatic anterior shoulder dislocation. In one prospective study 6 of 20 male patients (age range 18 to 22 years), Aronen and Regan reported a return to unrestricted duty and sports participation without redislocation for 75% of cases with a rehabilitation program that emphasized strengthening for the muscles of shoulder internal rotation and adduction (mean follow-up of 35.8 months). Another study 107 of 104 patients (mean age ± SD = 21.5 ± 8.5 years) reported a success rate of 83% with a 6-week graduated exercise regime of limited abduction (mean follow-up of 156 months).…”
Section: Nonoperative Management Of Dislocationmentioning
confidence: 99%
“…Traditionally, nonoperative intervention with a period of immobilization and physical therapy has been the preferred treatment for patients with a first-time incident of anterior shoulder instability with recurrences rates reported as low as 25% in young active males [65]. While the indications for operative intervention in young, active, males with first-time Fig.…”
Section: Physical Therapymentioning
confidence: 99%